2008
DOI: 10.1080/10428190801959018
|View full text |Cite
|
Sign up to set email alerts
|

Acute myeloid leukemia in four patients with t(8;21) treated with all-trans retinoic acid as a single agent

Abstract: Acute myeloid leukemia (AML) is characterized by a block of terminal differentiation of hematopoietic precursors and the repression of normal hematopoiesis by expanding immature blasts. AMLs are frequently associated with specific chromosomal translocations, resulting in the generation of chimeric genes. These genes encode chimeric transcription factors, which possess chromatin-modeling activity and deregulate the transcription of specific target genes [1].The use of all-trans retinoic acid (ATRA) has signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Clear experimental validation of these results is required and the approach that we are currently pursuing involves exposure of primary blasts obtained from AML patients to ATRA in vitro. Nevertheless, it must be emphasized that the validity of the predictions on ATRA sensitivity based on our model is fully supported by the results obtained in the two above-mentioned clinical studies 8,9 . Finally, it should be mentioned that it is entirely possible that our analysis may overlook specific subgroups of patients or individual cases that may be sensitive to ATRA.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…Clear experimental validation of these results is required and the approach that we are currently pursuing involves exposure of primary blasts obtained from AML patients to ATRA in vitro. Nevertheless, it must be emphasized that the validity of the predictions on ATRA sensitivity based on our model is fully supported by the results obtained in the two above-mentioned clinical studies 8,9 . Finally, it should be mentioned that it is entirely possible that our analysis may overlook specific subgroups of patients or individual cases that may be sensitive to ATRA.…”
supporting
confidence: 77%
“…As for the AML classification based on the presence/absence of the most prevalent genetic rearrangements, the cases showing an inversion of chromosome 16 [ inv(16) ] or a t(8;21) chromosomal translocation are characterized by ATRA-21 predictions well above the average of the remainder AML population. With respect to this, it is interesting to notice that a case report study demonstrates that ATRA induces one partial and three complete remissions in four t(8;21) AML patients initially misdiagnosed as APL cases 9 . As for the AML subtypes defined by recurrent gene mutations, the only cluster predicted to be responsive to ATRA belongs to the larger group of patients characterized by biallelic mutations of the CEBPA gene.…”
mentioning
confidence: 99%
“…Interestingly, one patient who had a temporary response (without CR) with ATRA achieved CR after a combined treatment including daunorubicin and cytarabine. The presence of both AML1-ETO and PML-RARα fusion genes were detected by RT-PCR in this patient [23]. The authors suggested that AML1-ETO and PML-RARα recruit a multiprotein complex containing histone deacetylases (HDACs) on crucial myeloid differentiation via several co-repressors, which leads to a cell differentiation block [24].…”
Section: Discussionmentioning
confidence: 99%
“…Griggs et al described one patient with normal cytogenetic-AML who was refractory to standard induction chemotherapy, but who entered a remission upon treatment with ATRA 45 mg/m2/day for 34 days 23 . Qian et al reported the effects of single-agent ATRA in four t(8;21) AML patients who were originally misdiagnosed as APL 24 . In one case, a patient was treated with arsenic trioxide for 50 days with no response; he was thereafter transitioned to 40 mg/d ATRA, and cleared his marrow of blasts within one week, but relapsed three weeks later.…”
Section: Atra and Myeloid Differentiationmentioning
confidence: 99%